Participatory plant breeding: Proceedings of a workshop on participatory plant breeding, 26-29 July 1995, Wageningen, The Netherlands - Hardon, J. (1995)
The outcome of a workshop on participatory plant breeding sponsored by IDRC, IPGRI, FAO and CGN. The objective was to develop a strategy for alternative approaches to classical centralized plant breeding.